The Concept of the Soul in the Cognitive Sciences. - Bremer, Józef (Filozofia Chrześcijańska, 2010)
Do the traditional, commonsense and philosophical concepts of the soul have any place in the contemporary cognitive sciences, which start from the premise that everything is scientifically explainable using naturalistic categories? To answer this question we should mention that most cognitive naturalists today - philosophers and scientists - are materialists, and methodological materialism is probably universally accepted among scientists these days. It is very difficult to find a place in such a picture of the world for the soul as it appears in our commonsense picture of how things are. It is the tension between these two pictures that generates the contemporary problems connected with the soul. In order to try to resolve this tension we first describe the concept of the soul and its close connection with the organic body. Then we present a critical characterisation of two things: 1) the development of the empirical sciences - Galen, Descartes, Newton, Gall, Galvani - and the resulting eliminativistic implications for the philosophical concept of the soul; 2) a pair of naturalistic philosophical explanations of the soul-body problem: the nonreductionist view of the soul and the eliminative materialist view. The third part of the article involves giving a short answer to the question of how Aristotle's doctrine regarding the soul is based on his attempt to explain internal and external movement. After that we compare his explanation of these forms of movement with two kinds of contemporary neurological explanation: a) that of the neurologist R. Llinas, who, for explanatory purposes, postulates the existence of a theoretical (i.e. epiphenomenal) self; b) the more realistic explanation presented by the neurologist A. Damasio, who posits three different versions of the self, before trying to link them to corresponding parts of the human brain that, in turn, are closely connected with the body. It can then be shown that there are several similarities between Aristotle's conception of the soul and Damasio's cognitivist conception of the self, and that, because of the different starting points and explanatory goals involved, the contemporary concept of the self does not completely exclude the traditional concept of the soul.